Digital Skills and Digital Safety on Digital Literacy of Female Entrepreneurs and Their Impact on MSME Performance in Purbalingga Regency - Pratiwi, Agustin Riyan; Supriyatin, Dyah; Pangestu, Retno; Putri, Adelia Fatwa Meautia (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
The world has now entered the digital era in all aspects, including in entrepreneurial activities. This Increases Pressure On demands that MSME (Micro, Small, and Medium Enterprises) transform into the digital realm. 65% of entrepreneurs in Indonesia are women, totaling 37 million people, which calls for more attention to be given to knowledge regarding digital literacy, digital skills, and digital safety. This is essential to maximize business performance by developing potential through proficiency and security in optimizing digital tools. This was proven through research conducted on 72 female entrepreneurs who are members of the Muslimah Entrepreneur (ME) community in Purbalingga Regency. SPSS 25.0 was used with a quantitative approach. The outcomes of the tests demonstrate that digital literacy has a significant impact on digital safety for female entrepreneurs, and both have a significant influence that directly affects MSME performance. Meanwhile, the relationship between digital literacy and digital skills, as well as between digital skills and MSME performance, did not show a significant impact.